2007
DOI: 10.1002/mrd.20816
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA expression patterns of histone‐associated genes in bovine preimplantation embryos derived from different origins

Abstract: Histone modification genes in bovine embryos: The mRNA expression pattern of histone-related genes was determined in bovine oocytes and embryos. We compared immature and in vitro-matured oocytes, either before or after enucleation and activation, in vitro produced embryos (zygotes, 8-16 cell stages, blastocysts), embryos cloned with female or male donor cells; parthenogenetic embryos, and in vivo-derived blastocysts to detect deviations from the normal expression pattern. A sensitive semi-quantitative endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Similar findings were made for ZAR1, an important maternal effect gene regulating early embryonic development (Duranthon & Renard 2001, Brevini et al 2004. ZAR1transcripts have been found in immature oocytes and in early embryos until major activation of the embryonic genome (Brevini et al 2004, Nowak-Imialek et al 2008). …”
Section: Discussionsupporting
confidence: 76%
“…Similar findings were made for ZAR1, an important maternal effect gene regulating early embryonic development (Duranthon & Renard 2001, Brevini et al 2004. ZAR1transcripts have been found in immature oocytes and in early embryos until major activation of the embryonic genome (Brevini et al 2004, Nowak-Imialek et al 2008). …”
Section: Discussionsupporting
confidence: 76%
“…41 Remarkably, accompanying with meiotic maturation, the relative abundance of SUV39H1 dramatically decreased in mouse and bovine oocyte. 69,70 G9A transcripts were absent in immature and matured mouse oocytes 70 and downregulated in bovine oocytes. 41,69 PcG proteins enhancer of zeste2 (EZH2) is one of HMTs responsible for methylating H3/K27.…”
Section: Regulation Of Histone Modifications In Mammalian Oocytementioning
confidence: 95%
“…69,70 G9A transcripts were absent in immature and matured mouse oocytes 70 and downregulated in bovine oocytes. 41,69 PcG proteins enhancer of zeste2 (EZH2) is one of HMTs responsible for methylating H3/K27. 71 Park et al found that the expression of EZH2 mRNA slightly reduced during porcine oocyte maturation.…”
Section: Regulation Of Histone Modifications In Mammalian Oocytementioning
confidence: 95%
“…The gene expression of embryos and fetuses produced by normal fertilization with sperm in comparison with embryos produced by NT shows numerous differences (Wrenzycki et al, 2001;Nowak-Imialek et al, 2008;Perecin et al, 2009). Conservation of appropriate DNA methylation patterns appears to be a problem in NT embryos (Bourc'his et al, 2001;Kang et al, 2002;Cezar et al, 2003;Santos et al, 2003).…”
Section: Introductionmentioning
confidence: 99%